The Effect of Sales Growth, Free Cash Flow, Operating Capacity, and Liquidity on Financial Distress - Astuti, Widia; Hariyanto, Eko; Pramono, Hadi; Inayati, Nur Isna (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Financial distress describes the condition of the company's financial decline before it went bankrupt. This research aims to test the influence of Sales Growth, Free Cash Flow, Operating Capacity, and Liquidity on Financial Distress in state-owned companies listed on the Indonesia Stock Exchange in 2019-2022. This type of research is a quantitative study with secondary data obtained from the Indonesian Stock Exchange. The sampling method in this study used a purposive sampling method that produced 43 observation samples at state-owned companies in 2019-2022. Tests in this study used multiple linear regression analysis methods with SPSS as a research test tool. Research results show that Sales Growth and operating capacity do not significantly affect financial distribution. Meanwhile, free cash flow and liquidity significantly positively affect financial distribution.